Sexual Abuse Exposure Alters Early Processing of Emotional Words: Evidence from Event-Related Potentials - Grégoire, Laurent; Caparos, Serge; Leblanc, Carole-Anne; Brisson, Benoit; Blanchette, Isabelle (Frontiers in Human Neuroscience, 2018)
This study aimed to compare the time course of emotional information processing between trauma-exposed and control participants, using electrophysiological measures. We conceived an emotional Stroop task with two types of words: trauma-related emotional words and neutral words. We assessed the evoked cerebral responses of sexual abuse victims without post-traumatic stress disorder (PTSD) and no abuse participants. We focused particularly on an early wave (C1/P1), the N2pc, and the P3b. Our main result indicated an early effect (55-165 ms) of emotionality, which varied between non-exposed participants and sexual abuse victims. This suggests that potentially traumatic experiences modulate early processing of emotional information. Our findings showing neurobiological alterations in sexual abuse victims (without PTSD) suggest that exposure to highly emotional events has an important impact on neurocognitive function even in the absence of psychopathology.